Ultrasound and Contrast-Enhanced Ultrasound Characteristics Associated With cN1 and Microscopic pN1 in Papillary Thyroid Carcinoma - Li, Wen; Qiu, Shusheng; Ren, Ling; Li, Qiuyang; Xue, Shaowei; Li, Jie; Zhang, Yan; Luo, Yukun (Frontiers in Endocrinology, 2022)
Objectives Lymph node metastases (LNMs) could be stratified into clinical N1 (cN1) and microscopic pN1 (pathological N1), which bear different biological behavior and prognosis. Our study aimed to investigate the associations between LNMs and primary tumor’s US (ultrasound) and CEUS (contrast-enhanced ultrasound) characteristics based on the stratification of LNMs into cN1 and microscopic pN1 in papillary thyroid carcinoma (PTC). Methods From August 2019 to May 2020, 444 consecutive PTC patients who underwent preoperative neck US and CEUS evaluation were included. According to regional lymph node status, the patients were classified into cN1 group versus cN0 (clinical N0) group and microscopic pN1 group versus pN0 (pathological N0) group. For multiple PTCs, the largest one was selected for the evaluation of US, CEUS and clinical features. Univariate and multivariate analyses were performed to determine independent predictors of cN1 and microscopic pN1. Results 85 cN1 versus 359 cN0 patients and 117 microscopic pN1 versus 242 pN0 patients were analyzed. Multivariate logistic regression analysis showed that <55-years-old (OR: 2.56 (1.08–6.04), male (OR: 2.18 (1.22–3.91)), large size (OR: 2.59 (1.71–3.92)), calcification (OR: 3.88 (1.58–9.51)), and hyper-enhancement (OR: 2.78 (1.22–6.30)) were independent risk factors of cN1, while <55-years-old (OR: 1.91 (1.04–3.51)), large size (OR: 1.56 (1.003–2.42)), multifocality (OR: 1.67 (1.04–2.66)) were independent risk factors of microscopic pN1. Conclusions For patients with PTC, young age, male, large size, calcification, and hyper-enhancement were independent predictors of cN1, while young age, large size and multifocality were independent predictors of microscopic pN1.